Missed injuries of the spinal cord. - Ravichandran, G (1982)
Damage to the spinal cord had not been recognised initially in 15 patients out of a consecutive series of 353 admitted over a decade to the National Spinal Injuries Centre with paralysis due to trauma to the cord. In some patients the missed diagnosis led to mismanagement and a greater neurological deficit. Missed injuries of the spinal cord are seen in patients with multiple injuries and head injuries and in those without any paralysis. Various radiological errors contribute to the failure to recognise the vertebral injury. In addition to causing severe disability to the victim these missed and mismanaged injuries of the spinal cord cost the National Health Service large sums in compensation. A careful evaluation of the history of each accident, with greater awareness of the potential of certain types of accidents to cause spinal cord injury, should reduce the incidence of missed injuries of the spinal cord.